Strategi Pemasaran Batu Bata di Kelurahan Sidomuly - Hanuarsyah, Dwi; Susena , Karona Cahya (Universitas Dehasen Bengkulu, 2024)
making bricks is a small business engaged in the building materials industry. The challenge that must be faced is how to increase product sales and introduce Batu Bata to the community. Therefore, a community service program with the title